2020
DOI: 10.3390/met10111441
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Condensation of Magnesium Vapor in Argon Carrier

Abstract: The nucleation and condensation of Magnesium (Mg) vapor carried by argon gas (Ar) were examined. The condensation of Mg vapor at a heat source temperature of 1273–1473 K and Ar flow rate of 0.1–0.4 m3/h was analyzed. The result indicated that the condensation temperature is affected by the heat source temperature and Ar flow rate, and the condensation temperature of Mg vapor was 1013.3 K at a heat source temperature of 1473 K and Ar flow rate of 0.2 m3/h. The effects of Mg vapor partial pressure and temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Jibiao Han et al [49,50] studied the nucleation and condensation mechanism of Mg vapor carried by argon and concluded that the condensation temperature of Mg vapor is influenced by the heat source temperature, the partial pressure of Mg vapor and the flow rate of argon. When the heat source temperature was 1473 K and the argon flow rate was 0.2 m 3 /h, the condensation temperature of magnesium vapor was 1013.3 K. The increase in Mg vapor supersaturation and the decrease in condensation temperature were favorable to the growth of liquid nucleation.…”
Section: Silico-thermal Methodsmentioning
confidence: 99%
“…Jibiao Han et al [49,50] studied the nucleation and condensation mechanism of Mg vapor carried by argon and concluded that the condensation temperature of Mg vapor is influenced by the heat source temperature, the partial pressure of Mg vapor and the flow rate of argon. When the heat source temperature was 1473 K and the argon flow rate was 0.2 m 3 /h, the condensation temperature of magnesium vapor was 1013.3 K. The increase in Mg vapor supersaturation and the decrease in condensation temperature were favorable to the growth of liquid nucleation.…”
Section: Silico-thermal Methodsmentioning
confidence: 99%
“…Yang et al [22] found that crystallization quality is improved by increasing the Mg partial pressure under appropriate condensation temperature and temperature gradient. In addition, Wang et al [23] investigated the condensation behavior of magnesium vapor under an argon atmosphere. They also found that a slight temperature gradient and high partial pressure of Mg vapor improved the liquid phase's nucleation rate and crystallization quality.…”
Section: Introductionmentioning
confidence: 99%